2016
DOI: 10.1177/1948550616652206
|View full text |Cite
|
Sign up to set email alerts
|

Wise Reasoning in the Face of Everyday Life Challenges

Abstract: How stable vs. dynamic is wisdom in daily life? We conducted a daily diary study of wise reasoning (WR) by recording people's reflections on daily challenges in terms of three facets: intellectual humility, self-transcendence, and consideration of others' perspectives/compromise. We observed substantial and systematic intraindividual variability in WR, with wiser reasoning in the social versus nonsocial contexts. State-level WR variability was potent in predicting a bigger-picture construal of the event, more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
137
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(154 citation statements)
references
References 65 publications
(132 reference statements)
9
137
1
1
Order By: Relevance
“…Similar to past research (Grossmann et al, 2016), we found moderate positive associations between Wave 1 and Wave 2, rSWIS (n = 290) = .48, rPerspectives (n = 290) =…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to past research (Grossmann et al, 2016), we found moderate positive associations between Wave 1 and Wave 2, rSWIS (n = 290) = .48, rPerspectives (n = 290) =…”
Section: Resultssupporting
confidence: 90%
“…Reliability and internal structure of wise reasoning were nearly identical to those from our initial tests. Study 7 showed a small-moderate degree of stability in wise reasoning across two distinct conflicts, indicating substantial intra-personal variation in wise reasoning across situations (as in Grossmann et al, 2016, and Study 2 in the current research).…”
Section: Study 7 Summarysupporting
confidence: 57%
See 3 more Smart Citations